Transplantation of mononuclear cells from human umbilical cord blood promotes functional recovery after traumatic spinal cord injury in Wistar rats - Rodrigues,L.P. (2012)
Cell transplantation is a promising experimental treatment for spinal cord injury. The aim of the present study was to evaluate the efficacy of mononuclear cells from human umbilical cord blood in promoting functional recovery when transplanted after a contusion spinal cord injury. Female Wistar rats (12 weeks old) were submitted to spinal injury with a MASCIS impactor and divided into 4 groups: control, surgical control, spinal cord injury, and one cell-treated lesion group. Mononuclear cells from umbilical cord blood of human male neonates were transplanted in two experiments: a) 1 h after surgery, into the injury site at a concentration of 5 x 10(6) cells diluted in 10 µL 0.9% NaCl (N = 8-10 per group); b) into the cisterna magna, 9 days after lesion at a concentration of 5 x 10(6) cells diluted in 150 µL 0.9% NaCl (N = 12-14 per group). The transplanted animals were immunosuppressed with cyclosporin-A (10 mg/kg per day). The BBB scale was used to evaluate motor behavior and the injury site was analyzed with immunofluorescent markers to label human transplanted cells, oligodendrocytes, neurons, and astrocytes. Spinal cord injury rats had 25% loss of cord tissue and cell treatment did not affect lesion extension. Transplanted cells survived in the injured area for 6 weeks after the procedure and both transplanted groups showed better motor recovery than the untreated ones (P < 0.05). The transplantation of mononuclear cells from human umbilical cord blood promoted functional recovery with no evidence of cell differentiation.